2000
DOI: 10.1002/1521-3773(20001215)39:24<4596::aid-anie4596>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Spirotryprostatin B and Three Stereoisomers

Abstract: Heck cyclization and trapping of the resultant η3‐allylpalladium intermediate by a tethered diketopiperazine is the central step in a new stereocontrolled route to spirotryprostatin alkaloids. The versatility of this approach is illustrated by the enantioselective total syntheses of the fungal natural product (−)‐spirotryprostatin B (1) and three stereoisomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(46 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…[1] Diverse elegant methods extensively complemented the fields of traditional coupling reactions and provided widely applicable approaches for new bond formation. [2] Efficient oxidative coupling protocols for functionalized indoles have been developed by the groups of Harran, [3] Danishefsky, [4] Trost, [5] Nicolaou, [6] Overman, [7] Muniz, [8] MacMillan, [9] Xiao, [10] Lei, [11] Vincent, [12] You, [13] Stephenson, [14] and others. [15] While, the synthetic utility of catalytic oxidative coupling cyclization for construction of complex benzofuroindolenines has not been fully developed.…”
Section: Abstract: Catalytic Oxidative Coupling Cyclization; Benzofurmentioning
confidence: 99%
“…[1] Diverse elegant methods extensively complemented the fields of traditional coupling reactions and provided widely applicable approaches for new bond formation. [2] Efficient oxidative coupling protocols for functionalized indoles have been developed by the groups of Harran, [3] Danishefsky, [4] Trost, [5] Nicolaou, [6] Overman, [7] Muniz, [8] MacMillan, [9] Xiao, [10] Lei, [11] Vincent, [12] You, [13] Stephenson, [14] and others. [15] While, the synthetic utility of catalytic oxidative coupling cyclization for construction of complex benzofuroindolenines has not been fully developed.…”
Section: Abstract: Catalytic Oxidative Coupling Cyclization; Benzofurmentioning
confidence: 99%
“…3). Assoanine (51), 105) pratosine (52), 106) hippadine (53), 107) and dihydroanhydrolycorin (54) 108) have been isolated from plants belonging to the Amaryllidaceae family. These alkaloids exhibit various biological activities, including acetylcholinesterase inhibitory activity, anticancer activity, and antitrypanosomal activity.…”
Section: Totalmentioning
confidence: 91%
“…In a similar manner, the tetracyclic compound 55b, which was obtained from carbamoyl chloride 58b by an oxindole formation, was converted to dehydroanhydrolycorine (54) using DIBAL-H. Hippadine (53) was also synthesized by the oxidation of dehydroanhydrolycorine (54). Spectroscopic data for the synthetic materials 51-54, including their high-resolution mass spectra, were consistent with those previously reported for these compounds.…”
Section: Totalmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] The results indicated that some analog(3) ( Figure 1) shows higher activity than the natural product itself. 17 Motivated by this, a variety of total syntheses of spirotryprostatin has been reported to date, such as oxidative rearrangement of chiral tetrahydro-β-carbolins, [17][18][19] an iminium ion intramolecular cyclization, 20,21 [ 25 cycloadditions, Mannich reactions, 26 intramolecular Heck reactions, 27,28 a nitroolefination strategy, 29 magnesium iodide catalyzed ring-expansion, 30 and a Pd-catalyzed prenylation. 27,31 In all cases, however, there are just a few literature reports referring to the synthesis of a spirotryprostatin scaffold, 11 which is structurally characterized by an indole moiety connected to a diketopiperazine moiety via the spiro quaternary carbon chiral center 32 (Figure 2).…”
mentioning
confidence: 99%